ISLAM, PEREMPUAN, DAN WACANA MODERNITAS DALAM RATU YANG BERSUJUD KARYA MAHDAVI DAN SERIAL JILBAB TRAVELER KARYA ASMA NADIA - Susanto, Dwi; Nugroho, Miftah; Wati, Rianna (Sunan Kalijaga State Islamic University Yogyakarta, 2022)
The issue of Islam, women, and modernity discourses are common discussions in Indonesian literature. Literary works can be seen as part of an effort to welcome these ideas. This study discusses the literary works of Mahdavi and Asma Nadia in responding to issues of Islam, women, and modernity discourse. This study uses a postcolonial study point of view. The object of this research is Ratu Yang Bersujud (2013) by Mahdavi and Hijab Traveler (2012, 2014, and 2015) series from Asma Nadia. The formal object is the discourse of colonial modernity, Islam, and women. The data of this research are the contents of literary works, colonial discourse, Islam, women, and modernity. The data interpretation technique was carried out by following the binary opposition reading procedure in postcolonial studies. The response to the discourse on women, Islam, and modernity is done by negotiating and at the same time building women's constructions. However, women's voices become ambiguous when the subject is trapped in the discourse of modernity and capitalism through the issue of globalization. Women must continue to play their Islamic identity in entering the arena of modernity.